2008
DOI: 10.1089/tmj.2007.0075
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management and Patient Outcomes Among Children and Adolescents Receiving Telemedicine Consultations for Obesity

Abstract: Rural residents report lower likelihood of exercising, and higher rates of obesity, heart disease, and diabetes compared to their urban counterparts. Our goals were to (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 40 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…Remote patient monitoring involves the transmission of personal health and medical data allowing a provider to track healthcare data, such as symptoms, vital signs, and/or laboratory data. Remote patient monitoring often utilizes mobile technologies and has also been shown to successfully result in care with outcomes similar to in-person outcomes for several chronic pediatric conditions, including asthma (26), diabetes (27), and obesity (28). All three of these telemedicine modalities have been used in caring for children with a variety of conditions in a variety of settings (8,16,(29)(30)(31).…”
Section: Overview Of Telemedicinementioning
confidence: 99%
“…Remote patient monitoring involves the transmission of personal health and medical data allowing a provider to track healthcare data, such as symptoms, vital signs, and/or laboratory data. Remote patient monitoring often utilizes mobile technologies and has also been shown to successfully result in care with outcomes similar to in-person outcomes for several chronic pediatric conditions, including asthma (26), diabetes (27), and obesity (28). All three of these telemedicine modalities have been used in caring for children with a variety of conditions in a variety of settings (8,16,(29)(30)(31).…”
Section: Overview Of Telemedicinementioning
confidence: 99%
“…3,4 Expert recommendations advocate a staged, family-based approach to pediatric obesity treatment. 5 As obesity levels persist, children and their families should participate in increasingly intensive treatments, culminating in referral to comprehensive interventions and tertiary-care clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, this study is consistent with previous research which has demonstrated that specialty telemedicine consultations can result in improved patient safety. 18,[39][40][41][42][43][44] …”
Section: Discussionmentioning
confidence: 99%